2022
DOI: 10.14814/phy2.15175
|View full text |Cite
|
Sign up to set email alerts
|

Acute mountain sickness and sleep disturbances differentially influence cognition and mood during rapid ascent to 3000 and 4050 m

Abstract: The impact of acute mountain sickness (AMS) and sleep disturbances on mood and cognition at two altitudes relevant to the working and tourist population is unknown. Twenty unacclimatized lowlanders were exposed to either 3000 m (n = 10; 526 mmHg) or 4050 m (n = 10; 460 mmHg) for 20 h in a hypobaric chamber. AMS prevalence and severity was assessed using the Environmental Symptoms Questionnaire (ESQ) and an AMS‐C score ≥ 0.7 indicated sickness. While sleeping for one night both at sea level (SL) and high altitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
(123 reference statements)
1
4
0
Order By: Relevance
“…S2 Table shows a comparison of those who have with those who have no AMS according to the LLS and the AMS-C score at the same time and location. The prevalences of AMS found in this study are in accordance with investigations reporting an AMS prevalence of about 4–7% for altitudes between 2850 and 3050 m [ 8 , 11 , 12 ], of 11% at 3400 m [ 13 ], and of 28.4% at 4559 m [ 9 ]. The altitude difference of 200 m between the lowest 2 huts (i.e., the Konkordia and Finsteraarhorn hut) did not increase the prevalence of AMS, as others had observed [ 6 , 8 , 14 ].…”
Section: Discussionsupporting
confidence: 92%
“…S2 Table shows a comparison of those who have with those who have no AMS according to the LLS and the AMS-C score at the same time and location. The prevalences of AMS found in this study are in accordance with investigations reporting an AMS prevalence of about 4–7% for altitudes between 2850 and 3050 m [ 8 , 11 , 12 ], of 11% at 3400 m [ 13 ], and of 28.4% at 4559 m [ 9 ]. The altitude difference of 200 m between the lowest 2 huts (i.e., the Konkordia and Finsteraarhorn hut) did not increase the prevalence of AMS, as others had observed [ 6 , 8 , 14 ].…”
Section: Discussionsupporting
confidence: 92%
“…The findings indicated that mild hypoxia had little influence on cognition compared to some of the classic symptoms of hypoxia (Pilmanis et al., 2016 ). Another study (Figueiredo et al., 2022 ) where 20 lowlanders who were not acclimatized to high altitude were exposed to either 3000 m or 4050 m for a duration of 20 h. The exposure was conducted in a hypobaric chamber. Results demonstrate that there was no significant difference between sea level group and high‐altitude group in cognitive performance.…”
Section: Resultsmentioning
confidence: 99%
“…These different points of interference between SD and responses to hypoxia make it possible to formulate hypotheses on the alteration of physiological tolerance, the risk of AMS, and the deterioration of cognitive performance, when these two constraints are combined ( Figure 1 ). In this sense, Figueiredo et al (2022) demonstrated that AMS symptoms have a greater negative impact on mood while poor sleep has a greater negative impact on cognition, in unacclimatized lowlanders exposed to either 3,000 m or 4,050 m for 20 h in a hypobaric chamber.…”
Section: Physiological and Cognitive Responses To Hypoxic Hypoxia Aft...mentioning
confidence: 97%
“…However, the prevalence of AMS is highly dependent on the study setting: for Luks et al (2017) it varies between 40% and 90%, depending on altitude and individual susceptibility, in unacclimatized individuals ascending more than 500 m per day at altitudes of 4,500–6,000 m, whereas it is ∼25%–40% when passively ascending at 3,000–3,500 m. Hypoxia also has detrimental neurobehavioral effects for unacclimatized humans: alterations in cognitive function, mood and sleep quality occur after a high-altitude climb ( Bahrke and Shukitt-Hale, 1993 ; Ainslie et al, 2013 ; Lombardi et al, 2013 ; McMorris et al, 2017 ). Interestingly, it has recently been shown that AMS and sleep disturbances differentially influence cognition and mood during rapid ascent (in a hypobaric chamber) to 3,000 and 4,050 m: the presence of AMS impacted mood while poor sleep impacted cognition ( Figueiredo et al, 2022 ).…”
Section: Physiological and Cognitive Responses To Systemic Environmen...mentioning
confidence: 99%